Principles of Management Accounting of Expenses and Their Improvement - Mukoviz, Vasyl (Zasady rachunkowości zarządczej ukierunkowanej na wydatki i możliwości jej usprawnień, 2010)
Accounting and administrative cost management model may include the following components: measurement of business transactions, application of concepts of financial and management accounting, financial and communications information management accounting. The model should meet the requirements of information systems: an integrated performing of the functions of collection, storage, processing and providing of accounting information. It is closed; serves circle of persons responsible for management decisions; it has feedback module manager accounting.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 87-92
Keywords: principles; management accounting; expenses; improvement